Mental Health Challenges in Bangladesh Based on the Integrated Examination of Illicit Drug Use, Substance Abuse, Tobacco Consumption, and Escalating Suicidal Tendencies: A Comprehensive Review - Hasan, Md Rakibul (Bangladesh Journal of Infectious Diseases, 2024)
The confluence of worsening mental health, surging illegal drug use, growing tobacco usage, and intensifying suicidal behavior indicates a significant public health catastrophe in Bangladesh. These difficulties are closely interconnected in the country's fast evolving socio-health environment, where rapid sociocultural changes, increasing urbanization, and substantial economic pressures are restructuring the social framework. The consequences of these shifts have wide-ranging repercussions, indicating a highly worrisome path for public health in the country. To effectively tackle these intricate and interwoven problems, it is necessary to possess a sophisticated and all-encompassing comprehension of their intertwined nature. This research explores the complex nature of these public health issues, emphasizing the immediate need for comprehensive and culturally sensitive approaches that are particularly designed for the unique circumstances of Bangladesh. The research highlights the need of creating treatments that are both successful in treating urgent issues and sustainable in promoting long-term health and stability in the country, taking into account the wider social, cultural, and economic factors involved. Bangladesh Journal of Infectious Diseases, June 2024;11(1):65-70